Effects of the intensified frequency and time ranges on consonant enhancement in bilateral cochlear implant and hearing aid users - Yoon, Yang-Soo; Drew, Carrie (Frontiers in Psychology, 2022)
Yoon demonstrated (Yoon, 2021) that consonant recognition improved significantly in normal hearing listeners when useful frequency and time ranges were intensified by 6 dB. The goal of the current study was to determine whether bilateral cochlear implant (BCI) and bilateral hearing aid (BHA) users experienced similar enhancement on consonant recognition with these intensified spectral and temporal cues in noise. Ten BCI and ten BHA users participated in a recognition test using fourteen consonants. For each consonant, we used the frequency and time ranges that are critical for its recognition (called “target frequency and time range”), identified from normal hearing listeners in Yoon’s study (2021). Then, a signal processing tool called the articulation-index gram (AI-Gram) was utilized to add a 6 dB gain to target frequency and time ranges. Consonant recognition was unilaterally and bilaterally measured under two signal processing conditions, unprocessed and intensified target frequency and time ranges at +5 dB and +10 dB signal-to-noise ratio and in quiet conditions. We focused on three comparisons between the BCI and BHA groups: (1) AI-Gram benefits (i.e., after-before intensified target ranges by 6 dB gain), (2) enhancement in binaural benefits via the AI-Gram processing, and (3) reduction in binaural interferences via the AI-Gram processing. Results showed that the mean AI-Gram benefit was significantly improved for the BCI (max 5.9%) and BHA (max 5.2%) groups. However, the mean binaural benefit was not improved after AI-Gram processing. Group differences in either the AI-Gram benefits or binaural benefits were not significant. Individual data showed wide ranges of both AI-Gram benefit (max -1% to 23%) and binaural benefit (max -7.6% to 13%) for both groups. Individual data also showed a decrease in binaural interference in both groups after AI-Gram processing. These results suggest that the frequency and time ranges, intensified by the AI-Gram processing, contribute to consonant enhancement for unilateral or bilateral listening and both BCI or BHA technology. The intensified frequency and time ranges helped to reduce binaural interference but contributed little to the synergistic binaural benefit in consonant recognition for both groups.